Pengaruh Gaya Kepemimpinan, Budaya Organisasi Dan Disiplin Kerja Terhadap Kinerja Karyawan PT.Timah Industri Di Cilegon - Anggie Rohima Rullah; Nurhajati Nurhajati; Muhammad Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine the influence of leadership style, organizational culture and work discipline on the performance of PT. Tin Industry in Cilegon. This study used a quantitative approach. The population in this study is employees of PT Timah Industri. The sampling method uses the Slovin formula because in sampling, the number must be representative so that the results of the study can be generalized, in this study the sample amounted to 60 respondents. The analysis technique uses Multiple Linear Regression Analysis. The results showed that the variables of influence of leadership style (X1), organizational culture (X2) and work discipline (X3) contributed to employee performance variables (Y) by 73.5% and the remaining 26.5% was explained by other independent variables that were not in the study. And simultaneously and partially the influence of leadership style, organizational culture and work discipline has a significant effect on employee performance. Keywords : Influence Of Leadership Style, Organizational Culture, Work Discipline, Employee Performance.